2022
DOI: 10.1097/pas.0000000000001927
|View full text |Cite
|
Sign up to set email alerts
|

Superficial CD34-Positive Fibroblastic Tumor

Abstract: Superficial CD34-positive fibroblastic tumor (SCD34FT) is a rare soft tissue neoplasm that shows overlapping features with PRDM10-rearranged soft tissue tumor (PRDM10-STT). This study characterizes the clinicopathologic, immunohistochemical, and molecular features of SCD34FT in a series of 59 cases. Fluorescence in situ hybridization to assess for PRDM10 rearrangement was performed in 12 tumors. Immunohistochemistry for CADM3 and WT1 was performed; CADM3 was also assessed in histologic mimics. Our cohort of 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Mitotic activity is generally low; however, atypical mitotic figures can sometimes be seen 7 . Recent studies have identified positive CADM3 immunohistochemical staining in up to 95% of both tumors regardless of PRDM10 rearrangement 3,6,7 . Anderson et al also recently described WT1 positivity in 75% of SCD34FTs and in all tumors with the PRDM10 rearrangement 7 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Mitotic activity is generally low; however, atypical mitotic figures can sometimes be seen 7 . Recent studies have identified positive CADM3 immunohistochemical staining in up to 95% of both tumors regardless of PRDM10 rearrangement 3,6,7 . Anderson et al also recently described WT1 positivity in 75% of SCD34FTs and in all tumors with the PRDM10 rearrangement 7 .…”
Section: Discussionmentioning
confidence: 97%
“…Both tumors exhibit diffuse CD34 positivity, and a subset may also be positive for pan‐keratin and desmin 3 . Mitotic activity is generally low; however, atypical mitotic figures can sometimes be seen 7 . Recent studies have identified positive CADM3 immunohistochemical staining in up to 95% of both tumors regardless of PRDM10 rearrangement 3,6,7 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations